Impact of Drought, Heat, Excess Light, and Salinity on Coffee Production: Strategies for Mitigating Stress Through Plant Breeding and Nutrition - Lucélia Borgo; Flávio Henrique Silveira Rabêlo; Paulo Eduardo Ribeiro Marchiori; Luiz Roberto Guimarães Guilherme; Leonor Guerra-Guimarães; Mário Lúcio Vilela de Resende (Agriculture)
Abiotic stresses significantly disrupt plant physiology at the molecular, biochemical, and morphological levels, often causing irreversible damage. To ensure sustainable coffee production, it is essential to understand how environmental stresses—such as drought, heat, excess light, and salinity—affect plant growth, and to develop strategies to mitigate their impact. Despite the limited number of studies on this topic, compiling existing knowledge can provide valuable insights into how coffee plants respond to such stresses. Specifically, understanding whether coffee plants can endure damage caused by these stresses and the mechanisms they employ to do so is critical. This review aims to (i) summarize key findings on the effects of drought, heat, excess light, and salinity on coffee plants and their coping mechanisms; and (ii) explore plant breeding and nutrition as potential strategies to mitigate these abiotic stresses and enhance coffee production.